Optimizing Organizational Commitment - Hidayat, M. Ilham; Farida Ferine, Kiki (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
In this era of globalization, quality human resources are needed and become capital for the business world to continue to grow and prosper. To achieve results that meet expectations, human resource development must be pursued as closely as possible. Supervision is essentially a function inherent in a leader or top management in any organization, along with other basic management functions such as planning and implementation. This research was conducted with the aim of examining the influence of supervision and work climate on organizational commitment with work discipline as an intervening variable at the Bank Indonesia Representative Office, North Sumatra Province. The results of this research are as follows: Work Discipline has a positive and insignificant effect on Organizational Commitment with the original sample being 0.126 and p value 0.289. Work Climate has a positive and significant effect on Work Discipline with an original sample value of 0.264 and ap value of 0.012. Work Climate has a positive and significant effect on Organizational Commitment with an original sample value of 0.525 and ap value of 0.004. Supervision has a positive and significant effect on work discipline with an original sample value of 0.639 and ap value of 0.000. Supervision has a positive and insignificant effect on Organizational Commitment with an original sample value of 0.131 and ap value of 0.251. Work Climate has a positive and insignificant effect on Organizational Commitment through Work Discipline with an original sample value of 0.033 and an ap value of 0.312. Supervision has a positive and insignificant effect on Organizational Commitment through Work Discipline with an original sample value of 0.081 and an ap value of 0.293.